Learning Management and Its Effect on Improving the Quality of Education - Daman Rasman Syarif Hidayat (International Journal of Science and Society, 2021)
The rapidly changing time has brought changes, including education, to every aspect of life. Education must constantly make changes to improve the quality of education as one of the formal educational institutions for the community. In this study the types of case studies are qualitative. Interviews and literary studies, field observations, and documentation were used for data collection techniques in this study. In this study, the analysis coincided with data collection on the ground. The investigator reduces data obtained in the field by analyzing the data, sorting each information by the focus of research and drawing conclusions in each direction. This study shows that improvements in the quality of education must be based on alternative management of schools. This promotes the development of the concept of quality management based on schools. This alternative management allows schools to be independent and regulated to improve the quality of education but still refers to national policies.